Comparación de consumo y costo de imipenem/cilastatina en los servicios de medicina interna del Hospital Nacional Edgardo Rebagliati Martins y Almanzor Aguinaga Asenjo, enero - diciembre del 2007 - Guevara Salazar, Mónica de Lourdes (2008)
The present investigation Type II: "Comparison of consumption and cost of Imipenem / Cilastatin in Internal Medicine of the National Hospital Edgardo Rebagliati Martins and Almanzor Aguinaga Asenjo January to December 2007," a study is retrospective and court General Objective whose cross is to compare the cost of consumption and Imipenem/Cilastatin in Internal Medicine. The Universe sample consisted of patients hospitalized in Internal Medicine Services attended from 01 January 2007 to December 31, 2007. The cost and consumption data were extracted from the database management system of hospital pharmacies in Single Dose of both hospitals. Consumption of Imipenem / Cilastatin in Internal Medicine of the National Hospital Edgardo Rebagliati Martins and Almanzor Aguinaga Asenjo was: DDD/100 4.69 beds / day and DDD/100 3.03 Beds / day respectively, and had a tendency statistically significant increase.The spending Imipenem / Cilastatin in Internal Medicine of the National Hospital Edgardo Rebagliati Martins and Almanzor Aguinaga Asenjo was: S/. 331 393.44 y S/. 29 786.30 Respectively, accounted for 2.35 % compared to the annual expenditure on anti-infectives